Integrated analysis of socio-ecological impacts on underground food storage in Beringia - Kazuyuki Saito; Yu Hirasawa; Michael S Koskey; Yoko Kugo; Theresa John; Go Iwahana; Shirow Tatsuzawa (Environmental Research: Ecology)
Underground storage utilizing natural cold energy, a long tradition of communities in Beringia closely integrated within their lifeways, is challenged by malfunctions or difficulties in appropriate use, affecting food security and food sovereignty, and community wellbeing. Previous studies tend to center on physical aspects in individual ice cellar cases in permafrost zones. In this study, we investigated impacts of climate and socio-ecological changes on underground food storage through analysis of local community interviews and proactive dialogues between local community experts and scientists to illustrate (1) the roles of cold storage in supporting their sustainable foods and lifestyles, (2) the causes and factors related to the issue of dysfunction of and/or decrease in underground cold storage use and eventual decline in use, and (3) consequent losses and damages these changes brought. Thereby, we enhanced and applied a ‘Food Life History’ framework, a working hypothesis constructed to address human-environment issues in a holistic, multiperspectival, and integrated way. The results show that changes in underground cold storage practices are not caused by a single factor (e.g. climate change or permafrost degradation alone), but through a variety of agents that have influence on different time scales (e.g. colonization, globalization, food changes, technologies for subsistence). Included is a relational diagram depicting the interrelations of relevant factors impacting the role and functionality of underground cold storage practices of a tradition more than a century old. It will serve to provide suggestions for sharing ideas and intuitive understandings of current situations, and a template to address and examine key points and potential policy options for future planning with respect to the resilience and wellbeing of communities, fostering open and transparent discussion.